Self-care as the Basis of the Mobile Application for Patients with Chronic Coronary Syndromes - A. I. Laskova; M. Yu. Frolov; Yu. A. Orlova; Yu. M. Lopatin (Столичная издательская компания, 2022)
Aim. To evaluate the impact of a mobile application usage on the self-care skills, quality of life, adherence to treatment, as well as the psychological characteristics of comorbid patients with stable coronary heart disease.Material and methods. The study will include patients over 18 years of age with an established diagnosis of ischemic heart disease, exertional angina pectoris I-IV CCS functional class, who have the technical ability to use the mobile application "B2Doc: Angina" on their smartphone. This mobile application contains main components of recommendations for the management of coronary heart disease and monitoring of patient's well-being. The program is based on the previously developed and validated questionnaire of the self-care ability of patients with coronary artery disease. The mobile application includes advice of the day, tracking the dynamics of angina pectoris symptoms, blood pressure and pulse, a medication diary as well as educational material about coronary heart disease. The study will assess quality of life: general (SF-36) and angina-related (Seattle Angina Questionnaire), self-care skills using the Self-Care of Coronary Heart Disease Inventory questionnaire. The primary endpoints will be cardiovascular events (cardiovascular death, acute myocardial infarction, acute cerebrovascular accident, hospitalization with unstable angina or decompensated chronic heart failure) and death from all causes. Endpoints will be evaluated in 1, 3, 6 and 12 months after discharge.Expected results. We expect that the use of the mobile application "B2Doc: Angina" by patients will improve their self-care skills and quality of life, as well as increase awareness of the disease.Conclusions. The use of the newly developed mobile application "B2Doc: Angina" is a potential tool for the prevention and treatment of coronary heart disease. It represents a promising solution for the rapid implementation and expansion of telemedicine practice.